Biodegradation of Poly(Lactic Acid) Biocomposites under Controlled Composting Conditions and Freshwater Biotope - Brdlík, Pavel; Borůvka, Martin; Běhálek, Luboš; Lenfeld, Petr (Polymers, 2021)
The influence of additives such as natural-based plasticiser acetyl tributyl citrate (ATBC), CaCO3 and lignin-coated cellulose nanocrystals (L-CNC) on the biodegradation of polylactic acid (PLA) biocomposites was studied by monitoring microbial metabolic activity through respirometry. Ternary biocomposites and control samples were processed by a twin-screw extruder equipped with a flat film die. Commonly available compost was used for the determination of the ultimate aerobic biodegradability of PLA biocomposites under controlled composting conditions (ISO 14855-1). In addition, the hydro-degradability of prepared films in a freshwater biotope was analysed. To determine the efficiency of hydro-degradation, qualitative analyses (SEM, DSC, TGA and FTIR) were conducted. The results showed obvious differences in the degradation rate of PLA biocomposites. The application of ATBC at 10 wt.% loading increased the biodegradation rate of PLA. The addition of 10 wt.% of CaCO3 into the plasticised PLA matrix ensured an even higher degradation rate at aerobic thermophilic composting conditions. In such samples (PLA/ATBC/CaCO3), 94% biodegradation in 60 days was observed. In contrast, neat PLA exposed to the same conditions achieved only 16% biodegradation. Slightly inhibited microorganism activity was also observed for ternary PLA biocomposites containing L-CNC (1 wt.% loading). The results of qualitative analyses of degradation in a freshwater biotope confirmed increased biodegradation potential of ternary biocomposites containing both CaCO3 and ATBC. Significant differences in the chemical and structural compositions of PLA biocomposites were found in the evaluated period of three months.
Keywords: plasticiser; CaCO3; poly(lactic acid); biocomposites; freshwater biotope; nano-cellulose; aerobic biodegradation